Co2GeO4 nanocomposites with reduced graphene oxide and carbon nanotubes as high-performance anodes for Na-ion batteries. Issue 21 (6th April 2021) - Nawaz, Bushra; Ali, Ghulam; Ullah, Muhammad Obaid; Iqbal, Fauzia; Iftikhar, Faiza Jan; Mehboob, Sheeraz; Rehman, Ata-Ur; Abbas, Syed Mustansar
Abstract : The prepared nanocomposites show an enhanced electrochemical performance. Abstract : Heterostructure nanomaterials have attracted attention as potential anodes for sodium-ion batteries (NIBs), owing to their outstanding properties. In this work, a single-step facile hydrothermal route was adopted for the synthesis of Co2 GeO4, Co2 GeO4 /rGO, and Co2 GeO4 /MWCNT nanocomposites. The X-ray diffraction analysis reveals the spinel phase formation of Co2 GeO4, Co2 GeO4 /rGO, and Co2 GeO4 /MWCNTs. Scanning and transmission electron microscopy results depict the growth of pristine Co2 GeO4 and Co2 GeO4 /rGO nanocomposites in the nanoscale size with sharp-edge plate-like morphology, while plate-like particles in Co2 GeO4 /MWCNT nanocomposites are grown on the surface and inside MWCNTs. The chemical bonding, oxidation state of elements in the composition, and the presence of rGO and MWCNTs are confirmed by X-ray photoelectron spectroscopy. The galvanostatic measurements reveal that Co2 GeO4, Co2 GeO4 /rGO, and Co2 GeO4 /MWCNT electrodes exhibit specific capacities of 314, 425 and 475 mA h g −1 respectively at a rate of 0.05C. The rate capability and long cycle testing results show higher specific capacity and structural stability of Co2 GeO4 /MWCNT nanocomposites. Co2 GeO4 /MWCNT nanocomposites show a specific capacity of 108 mA h g −1 at a high current density of 6.4C. Sodium diffusion coefficient was calculated using a galvanostatic intermittent titration technique and values were calculated in the range of 10 −14 to 10 −16 cm 2 s −1 and 10 −13 to 10 −16 cm 2 s −1 for Co2 GeO4 /rGO, and Co2 GeO4 /MWCNTs, respectively, which are greater than the values of pristine Co2 GeO4 (10 −15 to 10 −17 cm 2 s −1 ). This indicates the improved sodium-ion diffusion kinetics of Co2 GeO4 /rGO and Co2 GeO4 /MWCNT nanocomposites, indicating their superior electrochemical performance to pristine Co2 GeO4 .